Pre-Hospital Burn Management Practices: A Scoping Review - I Gusti Ngurah Agung Indra Dinata Jaya Putra; I Ketut Swarjana; I Nengah Adiana; Anak Agung Istri Wulan Krisnandari (Babali Nursing Research, 2026)
Introduction: Burn injury remains a global health problem with high morbidity and mortality. Although appropriate pre-hospital burn first aid can reduce complications, community knowledge, attitudes, and practices regarding correct burn management remain inadequate.Methods: This literature review applied the PCC framework. The Population included communities and individuals; the Concept covered correct and incorrect burn first aid practices; and the Context focused on pre-hospital burn management. Eligible studies were experimental, cross-sectional, or cohort designs published in English or Indonesian within the past ten years and available in full text. Narrative, integrative, scoping, systematic reviews, and meta-analyses were excluded. Literature searches were conducted in PubMed and ScienceDirect using relevant keywords.Results: A total of 449 articles were initially identified from the PubMed and ScienceDirect databases. After screening, 313 articles remained, of which 86 were excluded. Of the 227 full-text reports assessed, 187 were inaccessible. Forty studies were then evaluated for eligibility, and 25 were excluded because they did not discuss burn first aid (n = 10), were not community-focused (n = 8), or were irrelevant to the pre-hospital context (n = 7). In total, 15 studies met the inclusion criteria. The findings revealed that community knowledge, attitudes, and practices regarding burn first aid were generally low.Conclusion: Pre-hospital burn management practices remain inadequate, with persistent misconceptions. Further research is needed to identify determinants influencing burn first aid behaviors to inform targeted community-based health education interventions.